The Effectiveness of Using Answer Garden Application as Brainstorming Activity in Online Learning - Ance Jusmaya (Fakultas Bahasa dan Seni UNP, 2022)
This research is based on the teaching online experience where the learning process becomes less interactive and the atmosphere during online learning was monotonous. By seeing the fact, the researcher is interested to apply an application that seem appropriate to help the students to improve their writing ability in online learning called Answer Garden. The purpose of this research is to solve the problems faced by lecturers who teach writing in universities in Batam. Answer Garden is a new minimalistic feedback tool used to stimulate real-time student participation, online brainstorming, and obtain classroom feedback. The research applied the qualitative research by using observation sheet, field notes, and questionnaire. The results showed that using Answer Garden as Brainstorming activity in online learning gives a good result where students are motivated by the concept because allowing them to generate lists, phrases, thoughts, words, ideas, or questions about a topic of writing in interactive ways. Thus, Answer Garden was seen as a great application to promote student participation during the online learning, because it can involve students brainstorming and collaborating on a topic question that the teacher asked during the online learning.